2001
DOI: 10.1086/323813
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Nasal Endoscopy versus Sinus Puncture and Aspiration for Microbiologic Documentation of Acute Bacterial Maxillary Sinusitis

Abstract: Sinus puncture and aspiration is an invasive procedure that hinders patient enrollment in studies of acute bacterial maxillary sinusitis (ABMS). Pain and minor bleeding also limit its potential diagnostic utility in clinical practice. Cultures obtained by rigid nasal endoscopy were compared with those from sinus puncture and aspiration in 53 patients with ABMS; 46 patients were assessable. Considering recovery of Haemophilus influenzae, Moraxella catarrhalis, or Streptococcus pneumoniae from puncture and aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 29 publications
(21 reference statements)
4
52
0
4
Order By: Relevance
“…Cultures from the OMC obtained with endoscopic guidance have shown no or minimal pathogenic bacteria in healthy adults, [4][5][6][7][8] reflecting the effectiveness of mucociliary clearance in preventing pathogenic bacteria from colonizing nasal and sinus mucosa. In contrast, in a study of OMC cultures compared to maxillary sinus puncture for documenting acute bacterial sinusitis, Talbot et al 9 found pathogenic bacteria in the OMC of 15 of 46 patients (33%) who were assessable.…”
mentioning
confidence: 92%
“…Cultures from the OMC obtained with endoscopic guidance have shown no or minimal pathogenic bacteria in healthy adults, [4][5][6][7][8] reflecting the effectiveness of mucociliary clearance in preventing pathogenic bacteria from colonizing nasal and sinus mucosa. In contrast, in a study of OMC cultures compared to maxillary sinus puncture for documenting acute bacterial sinusitis, Talbot et al 9 found pathogenic bacteria in the OMC of 15 of 46 patients (33%) who were assessable.…”
mentioning
confidence: 92%
“…Using endoscopic guidance, samples were collected directly from the osteomeatal complex, put on ice, and transferred to the lab. Endoscopically directed sampling of secretions from the osteomeatal complex have been shown to be an accurate representation for the properties of secretions from inside the sinuses, at least in terms of bacterial presence (37,38). Secretions from the left and right osteomeatal complexes were combined and centrifuged at 1,100 rpm at 4 °C for 5 min.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Se han hecho estudios comparando muestras de secreción obtenidas bajo visualización directa del meato sinusal mediante un endoscopio rígido, con muestras obtenidas por punción. Talbot estudió 46 pacientes con ambas técnicas, y observó 85,6% de sensibilidad y 90% de especificidad si consideraba solamente S. pneumoniae, Haemophilus sp y M. catarrhalis, obteniendo eso sí un mayor aislamiento de S. aureus que puede ser parte de la flora del meato [23][24][25][26] . Vogan obtuvo en 16 pacientes 90% de correlación.…”
unclassified